Pengaruh Model Pembelajaran Berbasis Inkuiri, Literasi Ekonomi, dan Lingkungan Belajar Terhadap Kemampuan Berpikir Kritis Siswa Dengan Motivasi Belajar sebagai Variabel Mediasi - Asmaul Husna; Inanna Inanna; M. Ihsan Said Ahmad; Hikmayani Subur; Sri Hutami Adiningsih S (CV. Ulil Albab Corp, 2026)
The purpose of this research is to identify the factors affecting students' critical thinking abilities at SMA Kartika XX-1 Makassar, including their learning motivation, the learning environment, economic literacy, and the inquiry-based learning model. This study used a descriptive analytic strategy and a quantitative methodology. Two hundred and fifty-seven tenth graders from SMA Kartika XX-1 Makassar made up the sample. The PLS-SEM, or Partial Least Square Structural Equation Model, was used for data analysis. The study's findings indicate that: (1) the inquiry-based learning paradigm is associated with intrinsic drive to learn; (2) a connection exists between financial literacy and the desire to study; (3) the setting for learning has an effect on students' desire to study; (4) Inquiry-based learning is associated with an increase in students' capacity for critical thinking; (5) Economic literacy correlates with pupils' capacity for analytical reasoning; (6) the classroom setting affects pupils' capacity for critical thinking; (7) students' critical thinking abilities are related to their learning motivation; (8) the connection between students' critical thinking abilities and the inquiry-based learning paradigm may be mediated by learning motivation; (9) students' critical thinking abilities are mediated by their learning motivation in the link between economic literacy and (10). Students' intrinsic willingness to study may moderate the connection between classroom setting and analytical reasoning abilities.